Medicine Pricing Policies: The Impact On Availability And Affordability In Four Provinces In Indonesia - Anggriani, Yusi (2013)
The government of Indonesia has established a commitment to the provision of affordable medicines. The retail price of unbranded generic cannot exceed the maximum retail price set by the Ministry of Health. The generic medicine pricing policy that has been implemented by the Indonesian government must be evaluated. The objectives of this study were to evaluate the impact on the price, availability and affordability of selected medicines and to evaluate the context, process, evidence and links of generic medicine pricing policies development in Indonesia. The first part of the study was conducted using a standardized methodology developed by the World Health Organization and Health Action International. The prices, availability and affordability of 50 medicines were measured at public, private and NGO facilities in four provinces in Indonesia (Sumatera Selatan, Jakarta, Yogyakarta and Sulawesi Selatan). The type of medicines selected were Lowest Price Generics (LPGs) and Innovator Brands (IBs). The 2009 International Reference Price (IRP) was used to calculate the median price ratio (MPR). The second part of the study was conducted using the following methods: a review of medicine pricing policies documents, in-depth interviews with 10 key informants and 10 observations of meetings about medicine prices. Transcripts were generated and analyzed using qualitative content analysis.